Optimum Design Model of Energy-Efficient Affordable Housing Units in UAE: Two Cases Study of Affordable Housing units in Dubai - Abuserdaneh, Waad (2020)
In response to UN-Sustainable Development goals to provide a sustainable and comfortable living for people in all society segments and to Sheikh Mohammed Bin Rashid 50-Year Charter vision to attain self-sufficiency in energy, food and water in most citizens homes, it is essential to explore and study process, strategies and methods that improve the energy performance and quality of living for the building especially the residential units, which achieve environmental, economic and social sustainability goals. The selected case studies of this research are housing units belonging to Mohammed Bin Rashid Housing Establishment and Sheikh Zayed Housing Programme Government organization. They aim to provide appropriate housing units for UAE nationals. The simulation software used to conduct the assessment method of the research is the IES-VE, where the base cases computational models created and analyzed regards the energy consumption performance. The base cases' simulation outcomes were used to develop refurbishment models based on various passive design strategies and renewable energy technologies. Which later analyzed in terms of the life cycle cost to identify the total expanses of the cases study developed models. A comprehensive comparison was carried out between the base case models and their developed sub-models to obtain the optimum model for the total life cycle cost and energy conservation. The outcomes indicate the possibility of designing and constructing energy-efficient housing units and affordable in terms of the life cycle cost throughout its lifespan. Moreover, the simulation results present that the models created based on the integration between the PV system technologies and passive design strategies significantly impact saving energy and reducing the life cycle cost of houses. An appropriate selection of construction material and lighting system plays a crucial role in minimizing electricity consumption for both cases overbuilding life cycle. Building energy performance indicates a significant enhancement when proper passive cooling design methods are implemented, such as shading devices, courtyard and green roof system.